STRUCTURAL AND STYLE APPROACH TO THE ORGANIZATION PERSONALITY-ORIENTED LEARNING (Pedagogy of Higher and Secondary Education, 2007)
The article covers the issues of correlation between normative and creating in the conditions of module-sectional organizations of educational information on creative faculties and priorities of realization of structural-stylish approaches to organization of the personality-oriented teaching of future teachersartists.